Flesh, tongue : poems - Yao, Yaya (Mawenzi House, 2015)
"In this first collection, Yaya Yao confronts her inherited fragmented self and her hunger for a home, using scraps of personal and communal memory to bridge languages, worldviews, and physical distance from her ancestoral homeland. Bits of Cantonese, Mandarin, Hokkien, and Shanghainese are translated and altered to explore the dynamics between language and identity."--Publisher